(untitled) (Bangladesh Journal of Otorhinolaryngology, 2020)
Otosclerosis is the most frequent cause of conductive hearing loss in patients with intact tympanic membrane. It can be treated by surgery with various techniques. Because of limited manipulation and comparably similar results, stapedotomy at present is preferred over other surgical techniques by most surgeons. Here we present the operative results of 35 otosclerotic patients who underwent stapedotomy between January 2009 - October 2010 in the department of Otolaryngology- Head & Neck Surgery of Bangabandhu Sheikh Mujib Medical University, Dhaka Medical College Hospital and Shahid Suhrawardhy medical college & hospital, Dhaka. The aim of this study was to evaluate the hearing results following stapedotomy in otosclerosis surgery. The average air-bone gap of patients improved significantly to 21.74 dB after operation. Other hearing parameters of patients (including air conduction, bone conduction, speech discrimination score, and tinnitus) also improved. No patient experienced persistent vertigo after the operation and pre operative tinnitus resolved in 12 out of 22 patients. Stapedotomy is a safe and effective modality for improving conductive hearing loss in otosclerotic patients. Bangladesh J Otorhinolaryngol; October 2019; 25(2): 85-93